2012
DOI: 10.1111/j.1540-8159.2011.03298.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Ranolazine to Facilitate Electrical Cardioversion in Cardioversion‐Resistant Patients: A Case Series

Abstract: RZ shows promise as a safe and convenient agent to facilitate EC in EC-resistant patients. It appears to be most effective in patients whose AF duration is known to be less than 3 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 36 publications
1
35
0
2
Order By: Relevance
“…Subsequently, a number of small exploratory clinical studies showed the effectiveness of ranolazine to terminate paroxysmal AF [81, 82] and prevent post-operative AF [83]. Ranolazine has been shown also to facilitate electrical cardioversion of AF in cardioversion-resistant patients [84] as well as to improve effectiveness of amiodarone to terminate paroxysmal AF [85]. …”
Section: Anti-arrhythmic Efficacy Of Late Sodium Current Inhibitionmentioning
confidence: 99%
“…Subsequently, a number of small exploratory clinical studies showed the effectiveness of ranolazine to terminate paroxysmal AF [81, 82] and prevent post-operative AF [83]. Ranolazine has been shown also to facilitate electrical cardioversion of AF in cardioversion-resistant patients [84] as well as to improve effectiveness of amiodarone to terminate paroxysmal AF [85]. …”
Section: Anti-arrhythmic Efficacy Of Late Sodium Current Inhibitionmentioning
confidence: 99%
“…A small-scale study of patients with new onset or paroxysmal atrial fibrillation (AF; most of whom had some structural heart disease) showed 72% (13/18 patients) conversion to sinus rhythm with high dose (2000 mg) ranolazine, suggesting that further evaluation of ranolazine for AF conversion is warranted [20]. A study of 25 patients with AF resistant to electrical cardioversion, found that 19 patients were successfully cardioverted within two attempts, following oral ranolazine administration [21].…”
Section: Introductionmentioning
confidence: 99%
“…A trend for reduced episodes of new‐onset AF was already mentioned in MERLIN‐TIMI 36 trial 14. Several subsequent reports highlight the positive effect of ranolazine against atrial fibrillation in specific populations: post‐CABG, for the conversion of recent‐onset atrial fibrillation or in cardioversion‐resistant patients 15, 22, 23, 24, 25, 26, 27, 28. Moreover, RAFFAELLO trial 29 demonstrated that ranolazine in doses of 500 and 750 mg reduced AF recurrences compared to placebo (borderline significance).…”
Section: Discussionmentioning
confidence: 86%